The Cultivation of Lettuce (Lactuca sativa L) The scale of a house without a yard Wall Garden Models and Media Types (Agrikan Jurnal Agribisnis Perikanan, 2022)
House without yard, can still produce vegetable crops through plant cultivation techniques in the wall garden. The wall garden plant cultivation technique is similar to conventional cultivation, only planting using containers from paralon pipes, bamboo sticks or bags, and how to put it attached or hung on the wall of the house.  The purpose of this study was to study the cultivation of lettuce (Lactuca sativa L) the scale of a house without a yard  wall garden models and media types. This study used a factorial randomized block design with three replications. Each treatment there are 5 sample plants, so the plants studied were 135 plants. The first factor is the wall garden model (M), namely M1 = bag model, M2 = paralon pipe model, M3 = bambo model, and the type of media (J), namely: J1 = a mixture of top soil, chicken manure and husks, J2 = mixture of top soil, goat manure and husk, J3 = a mixture of top soil, cow manure, and husk.  The results showed that the wall garden paralon model provided the best lettuce growth and production.  Media types from a mixture of top soil, sometimes chicken fertilizer, and husks provided the best lettuce growth and production. The interaction between the paralon model wall garden and the type of media from a mixture of top soil, sometimes chicken fertilizer and husks gave the best lettuce growth and production.
Keywords: lettuce, wall garden, media, verticulture